2013
DOI: 10.1021/nn401617u
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Responsive Microgels Integrated with Enzyme Nanocapsules for Closed-Loop Insulin Delivery

Abstract: A glucose-responsive closed-loop insulin delivery system represents the ideal treatment of type 1 diabetes mellitus. In this study, we develop uniform injectable microgels for controlled glucose-responsive release of insulin. Monodisperse microgels (256 ± 18 μm), consisting of a pH-responsive chitosan matrix, enzyme nanocapsules, and recombinant human insulin, were fabricated through a one-step electrospray procedure. Glucose-specific enzymes were covalently encapsulated into the nanocapsules to improve enzyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
272
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 368 publications
(277 citation statements)
references
References 31 publications
3
272
0
2
Order By: Relevance
“…The matrix can undergo structural transformations (i.e., shrink, swell, dissociate) regulated by glucose concentration changes, leading to glucose-stimulated insulin release (11)(12)(13)(14). The typical glucose-sensing moieties include phenylboronic acid (PBA), glucose-binding protein (GBP), and glucose oxidase (GO x ) (12)(13)(14)(15)(16)(17)(18)(19)(20). Despite these available sensing chemistries, the majority of existing synthetic closed-loop systems have only been studied in vitro, with relatively few showing applicability in vivo due to specific challenges for each glucose-sensing strategy.…”
mentioning
confidence: 99%
“…The matrix can undergo structural transformations (i.e., shrink, swell, dissociate) regulated by glucose concentration changes, leading to glucose-stimulated insulin release (11)(12)(13)(14). The typical glucose-sensing moieties include phenylboronic acid (PBA), glucose-binding protein (GBP), and glucose oxidase (GO x ) (12)(13)(14)(15)(16)(17)(18)(19)(20). Despite these available sensing chemistries, the majority of existing synthetic closed-loop systems have only been studied in vitro, with relatively few showing applicability in vivo due to specific challenges for each glucose-sensing strategy.…”
mentioning
confidence: 99%
“…As the level of glucose decreases, the pH returns to physiological levels, decreasing the release of insulin. These technologies are able to tune the blood glucose levels to desirable levels for longer periods of time relative to nonresponsive insulin delivery in a diabetic mouse model (48,49). Finally, insulin itself has been engineered with a glucose-binding switch, allowing for glucose-mediated activation of insulin in the blood in a single molecule formulation (50).…”
Section: Environment-responsive Nanosystemsmentioning
confidence: 99%
“…Scientists reported that microgels with enzyme nanocapsules enables insulin discharge and causes a decrease in blood glucose levels in a mouse model of Type I diabetes. The microgel system expanded when exposed to hyperglycemic environments acting as a regulator and releasing insulin as a consequence of the enzymatic transformation of glucose into gluconic acid and protonation of the chitosan network [41]. Scientists developed various micro-engineering techniques which is utilized to fabricate in vitro 3D (three-dimensional) islet models which can facilitate islet of pancreases in vivo under different physiological and pathological conditions i.e., clinical islet transplantation and different molecular mechanisms of diabetes [61].…”
Section: Diabetesmentioning
confidence: 99%
“…Number of studies have been reported in past few years related to the efficacy and safety of various nanoparticles like cholesteroltethered platinum II-based supramolecular nanoparticle [37][38][39][40][41], polymeric-ceramic nanocarriers (NCs) in order to achieve oral delivery of the anticancer neutraceutical iron-saturated bovine lactoferrin (Fe-bLf) protein) [42,43], novel alginate-enclosed chitosan-calcium phosphate-loaded iron-saturated bovine lactoferrin nanocarriers for oral delivery in colon cancer therapy etc. [44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%